A randomised trial of post-discharge enteral feeding following surgical resection of an upper gastrointestinal malignancy. Issue 6 (December 2017) - Froghi, Farid; Sanders, Grant; Berrisford, Richard; Wheatley, Tim; Peyser, Paul; Rahamim, Jo; Lewis, Stephen
Summary: Background: Patients undergoing upper gastrointestinal surgery often eat poorly post-operatively, despite dietetic input. A pilot study was conducted to examine the benefit of a 6 week nutritional supplementation via a feeding jejunostomy on fatigue, quality of life and independent living. Methods: A feeding jejunostomy was placed routinely at oesophagectomy or total gastrectomy for cancer. At discharge, patients were randomised to nutritional supplementation (600 kcal/day) via their feeding jejunostomies or no jejunal supplement. Patients were assessed at discharge and 3, 6, 12 and 24 weeks following discharge for fatigue (MFI-20), quality of life (QLQ-OES18), health economic analysis (EQ5D) as well as completing a two-day dietary diary. Results: 44 patients (M:F, 29:15) were randomised, 23 received jejunal supplements. There were no differences between the groups. Percentage of calculated energy requirement received was greater in the supplemented group at weeks 3 and 6 (p < 0.0001). Oral energy intake was not different between the groups at any time period. After hospital discharge, there were no differences in MFI-20, EQ5D and QLQ-OES18 scores at any time point. From hospital discharge fatigue improved and plateaued at 6 weeks (p < 0.05 for both groups), independence at 12 weeks (p < 0.05 for both groups). No improvement was seen in quality of life until 24 weeks in the active group alone (p < 0.02) and not at all in the control group. Conclusions: Addition of jejunal feeding is effective in providing patients with an adequate energy intake. Increased energy intake however, produced no obvious improvement in measures of fatigue, quality of life or health economics.